Study of psychological bases of leadership competency formation of managers of public health institutions - Lekhan V.N.; Kryachkova L.V.; Kanyuka G.S. (Medičnì Perspektivi)
Psychodiagnostic examination of 288 health care managers of Dnipropetrovsk region was conducted to determine communicative and organizational characteristics of health managers of different levels. CОS-1 technique was used to study communication and organizational skills. Leaders were divided into two groups of comparison by the level of their administration: 40.3% of head doctors of the first level of control and 59.7% of administrators of second-level management executives. Psychological characteristics were compared with the results of a similar study conducted by the same procedure in 2001. Mainly high degree of communication and organizational skills of managers of different ranks of officers was established. The results showed improvement of communicative and organizational skills of health care managers with time and with the level of managerial positions (p<0.05). Level of organizational skills exceeds the level of communicative skills of managers. Low level of communicative skills was observed in 16.81% of the respondents. This requires development of appropriate management skills for better achieve ment of the objectives of the health system, including its responsiveness.